Digital Luxury Fashion Shows: Leveraging Interactive Marketing Opportunities Through Social Media Sentiment Analysis - Farah, Maya F. (2024)
Luxury brands have been hesitant to embrace social media to a full extent; yet, the COVID-19 pandemic prompted many companies to accelerate their adoption of digital strategies. For the first time, fashion show presentations of new collections were reinvented to be virtually streamed. This innovative shift entails an urgent examination of consumers’ sentiment vis-à-vis digital fashion show videos streamed on each of the main social media platforms, namely: YouTube, Instagram, and Facebook. Sentiment analysis using supervised machine learning and lexicon-based were employed to test and identify the classification of 21,424 comments conveyed towards the different types of fashion shows. Five different types emerged from the examination of all scraped comments; (a) show configuration, (b) emotional connection, (c) geographical tagging, (d) referral/tagging, and (e) collection related. This paper is amongst the first to examine consumers’ sentiment towards digital fashion shows. The literature related to digital strategies based on the sentiment analysis conveyed towards luxury fashion shows is still nascent. This study fills a considerable gap in the literature regarding marketing strategies to be adapted per digital channel for luxury fashion runways.